Design and Technical Quality on The Smes Efficiency: Empirical Evidence From Batik SMEs in Central Java, Indonesia - Edy Dwi Kurniati; Sri Rahayu (Muhammadiyah University Press, 2021)
The research is aimed to analyze the effect of design and technical quality implementation on technical and economic efficiency in the batik SMEs (small medium enterprises) in the Central Java province, Indonesia. Implementation of the technical quality is measured by process management implementation. Implementation of the design quality is measured by access to the development of the batik designs quality. The data are collected by direct interview approach to 100 manager-owners of batik business. Efisiensi teknis dan ekonomi diestimasi melalui stochastic efficiency frontier analysis. Furthermore, analysis of the implementation of design and technical quality on technical and economic efficiency uses a regression analysis with dummy variables. Competitive strategy orientation was used as the control variable. The final results are: (1) the role of entrepreneurs in the implementation of design and technical quality does significantly on technical efficiency, (2) the entrepreneurs role in the implementation of design and technical quality does significantly increase economic efficiency. The application of quality management significantly increase economic efficiency primarily in companies with focus and differentiation strategy. Economic efficiency are higher in entrepreneurial implement design and technical quality, and using focused and differentiation strategy. The conclusion this study is the design and technical quality implementation has an effect on the batik SMEs revenue efficiency.